The Form, Senses And Dynamics: A Literature Review On The Philosophical And Technical Coherency For The Development Of The Floor-Sitting Furniture Design - M.Najib, Sani; B.Saiful, Yusoff (2016)
This paper presents the literature review of the philosophical and technical coherency on the postural behavior for the development of the floor-sitting furniture design. The review encompasses the discussion of space-form, human senses and postural dynamics, and ergonomics relationships to the subject of floor-sitting by citing significant works of scholars among the architects, psychologists and ergonomists that are related to the postural behavior subject. The elaboration of literature contents consists of existing information from cross-disciplinary studies that consequently forms the foundation to the acceleration of research activities, steering for the study of sitting behavior and the development of design within the perimeters of a home environment. The explanations given provide a larger spectrum to the body of knowledge, and lead to further investigations based on the integration of cross-disciplinary studies into other cultural behavior related studies that conceivably contribute to the benefit of researchers and educators at the academia level.